Firm-specific characteristics and environmental disclosure of energy firms in Sub-Saharan Africa - Orajekwe, Jerry Chukwuebuka; Ogbodo, Okenwa Cy (International Journal of Financial, Accounting, and Management, 2023)
Purpose: This study investigated the relationship between firm-specific characteristics and environmental disclosure practices of energy firms in sub-Saharan Africa. It examines how profitability, size, and liquidity influence the environmental disclosure index (EDI) of listed energy firms in the region. Research methodology: A quantitative approach was adopted, utilizing secondary data from the annual reports of energy firms listed in Nigeria, South Africa, and Kenya. Regression analysis was employed to assess the impact of firm-specific characteristics on EDI using waste management data based on the Global Reporting Initiative (GRI) 306 guidelines. Results: The findings indicated that Profitability positively affected EDI, indicating greater transparency in reporting environmental initiatives for more profitable firms. Conversely, firm size is negatively correlated with environmental disclosure, suggesting challenges for larger firms in effectively communicating their environmental efforts. However, firm liquidity did not significantly affect EDI. Limitations: One limitation of the study is its focus on energy firms in only three countries, limiting the generalizability of the findings to other sub-Saharan African nations. Contribution: This research contributes to the literature by addressing environmental disclosure practices within sub-Saharan Africa's energy sector, offering stakeholders, policymakers, and regulators insights to promote transparency and sustainability in the industry. Novelty: The novelty of this study lies in its examination of firm-specific characteristics and their influence on environmental disclosure practices in the energy sector of Sub-Saharan Africa. Using waste management data as a proxy for disclosure offers a fresh perspective on the reporting practices of energy firms in the region.